2023
DOI: 10.1098/rstb.2022.0434
|View full text |Cite
|
Sign up to set email alerts
|

Invade or die: behaviours and biochemical mechanisms that drive skin penetration in Strongyloides and other skin-penetrating nematodes

Courtney R. McClure,
Ruhi Patel,
Elissa A. Hallem

Abstract: Skin-penetrating nematodes, including the human threadworm Strongyloides stercoralis and hookworms in the genera Necator and Ancylostoma , are gastrointestinal parasites that are a major cause of neglected tropical disease in low-resource settings worldwide. These parasites infect hosts as soil-dwelling infective larvae that navigate towards hosts using host-emitted sensory cues such as odorants and body heat. Upon host contact, they invad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 127 publications
(260 reference statements)
0
1
0
Order By: Relevance
“…Also, itchy skin was found to be associated with intestinal parasitic infections (AOR [95% CI]: 5.99 [3.43–10.43]; p < 0.001). The result of this current study is consistent with those of other studies conducted among pregnant women and children found skin itching to be associated with intestinal parasites such as Strongyloides stercoralis and Hookworms ( Ancylostoma duodenale and Necator americanus ) 27,28 . It is important to note that unrelated factors such as allergic reactions, dermatitis, and insect bites among others can contribute to skin itching.…”
Section: Discussionsupporting
confidence: 91%
“…Also, itchy skin was found to be associated with intestinal parasitic infections (AOR [95% CI]: 5.99 [3.43–10.43]; p < 0.001). The result of this current study is consistent with those of other studies conducted among pregnant women and children found skin itching to be associated with intestinal parasites such as Strongyloides stercoralis and Hookworms ( Ancylostoma duodenale and Necator americanus ) 27,28 . It is important to note that unrelated factors such as allergic reactions, dermatitis, and insect bites among others can contribute to skin itching.…”
Section: Discussionsupporting
confidence: 91%
“…A crucial step in the life cycle of Strongyloides is finding and percutaneously entering a host individual. Courtney McClure, Ruhi Patel and Elissa Hallem review the current knowledge of skin-penetration behaviour and the underlaying mechanisms for Strongyloides and for hookworms, which are phylogenetically rather distant nematode parasites with similar infection biology (McClure et al [34]).…”
mentioning
confidence: 99%